PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP HARGA SAHAM PADA PERUSAHAAN. (Sektor Industri Konsumsi Tahun 2019-2021) - Hermiliani Olpah; Sri Murni; Indrian Supheni; Dwi Feby Sistyaningrum (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2023)
Abstract: Every year the share price of Manufacturing Companies fluctuates. This incident is due to several factors, namely internal factors and external factors. This research aims to find out whether internal factors consisting of ROA and EPS have an effect on stock prices and whether external factors consisting of the exchange rate and inflation have an effect on stock prices. This research uses quantitative research methods with a sample size of 51 consumer industry manufacturing companies registered on the IDX in the period 2019 - 2021. The data obtained were analyzed using the Statistical Program for Social Science. From the results of the hypothesis test, it was concluded that in particular ROA, EPS, Exchange Rates and Inflation had a positive and significant effect on share prices because the t value for the Return On Assets (X1) variable was 2.691 with a significance level of 0.095. This shows that t count > t table (2.691 > 2.013). The t value for the Earning Per Share (X2) variable is 3.248 with a significance level of 0.190. This shows that t count > t table (3.248 > 2.013). The t value for the Exchange rate variable (X3) is 2.763 with a significance level of 0.805. This shows that t calculated > t table (2.763 > 2.013). The t value for the Inflation variable (X4) is 2.575 with a significance level of 0.449. This shows that t calculated > t table (2.575 > 2.013). And based on the calculated F value of 11,971 > F table 2.57, then in accordance with the basis for decision making in the F test it can be concluded that the hypothesis is accepted or the variables Return On Assets (X1), Earning Per Share (X2), Exchange Rate (X3) and Inflation (X4) simultaneously influences the Stock Price variable (Y).